Promoting artistic quality in rhythmic gymnastics: a didactic analysis from high performance to school practice - Monique LOQUET (Escola de Educação Física e Esporte da Universidade de São Paulo (EEFEUSP), 2016)
Abstract In France, the curricula for physical education (PE) place gymnastic activities in a set of competences named "Achieving a corporal performance for artistic and acrobatic aims", alongside dance and circus arts. What place does Artistic occupy in gymnastic activities? Is an aesthetic gesture sufficient to be considered as part of an artistic activity? Defining the term «Artistic» is difficult in the field of sports, as descriptions usually come from the technique/Artistic dichotomy. Our analysis focuses on rhythmic gymnastics (RG), which is precisely seen as emblematic of this technique/Artistic division: on the one hand, technical rigor, prescriptions and rules; on the other hand, grace, creation and self-expression. We believe such compartmentalized categories are too schematic to define gymnasts' and students' activities, so we will examine their articulation points. We first present an overview of RG as a school practice in ordinary forms of teaching, then an historical analysis of RG as a sports practice, to highlight the unbridgeable gap between both school and sports practices, regarding technique/Artistic connections. We then propose three significant points of articulation (called games) closely combining technical requirements and artistic commitment. We consider that the variation of the three games played in GR (creating, making beautiful, representing) is the product of historical dynamics of this sport we call artistic. Finally, on this basis, we propose a learning game for novice students promoting the artistic quality of RG practice.